Environmental management in design : lessons from Volvo and Hewlett-Packard for the Department of Defense - Resetar, Susan A., 1961- (Rand, 1998)
The Defense Department, seeking methods to hold the line on environmental costs, can look to corporations in the private sector for novel approaches to environmental management. Corporations have learned that, if environmental issues are considered in the design stage, the payoffs over the life of the product or system can be large. The authors of this report concentrate on two corporations -- Volvo and Hewlett-Packard -- to identify the key factors that led to successful implementation of a design-for-environment program. The report shows, by drawing on the experience of Volvo, Hewlett-Packard, and other industry leaders, how DoD can incorporate pollution prevention into design activities of weapon systems without any loss of capability and with a potential for enormous savings.